Analisis terhadap Implementasi Akad Wadiah Yad Adh-Dhamanah pada Produk Simpanan Pendidikan di BMT Talaga-Majalengka - Bakri, Mukhlis; Rohmatul Farida, Rima (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2024)
The Wadiah Yad Adh-Dhamanah contract is one of the contracts used by BMT Talaga in Talaga Wetan Village, Talaga District, Majalengka Regency in its operations. The Wadiah Yad Adh-Dhamanah contract is applied to education savings products, where customers or members of BMT Talaga entrust their assets to the institution, and the institution may utilize the entrusted assets, from which it will fully benefit. The institution may provide bonuses to customers or members that were not previously promised at the time of the contract. However, the exact implementation of the Wadiah Yad Adh-Dhamanah contract in education savings products at BMT Talaga, as well as the Islamic law regarding this contract, is not yet known. This research aims to determine the implementation of the Wadiah Yad Adh-Dhamanah contract in education savings products at BMT Talaga. Additionally, this study also aims to analyze the Islamic legal perspective on the implementation of the Wadiah Yad Adh-Dhamanah contract in education savings products at BMT Talaga. This research is qualitative, utilizing field research methods. The data collection techniques include interviews and documentation. The results of this research are as follows: firstly, the practice of the Wadiah Yad Adh-Dhamanah contract in education savings products, which includes the deposit-taking for education savings and the bonuses provided by the institution. Secondly, the research indicates that the practice of the Wadiah Yad Adh-Dhamanah contract in education savings products at BMT Talaga in Talaga Wetan Village, Talaga District, Majalengka Regency, when viewed from the pillars and conditions of the contract, is in accordance with Islamic law, and the withdrawal system for savings is in line with Fatwa DSN MUI No. 02/DSN-MUI/IV/2000. However, the provision of bonuses for education savings is not in accordance with Fatwa DSN-MUI No. 02/DSN-MUI/IV/2000 because the bonuses for education savings at BMT Talaga are predetermined at the outset.